Measuring risk aversion with lists: A new bias - Antoni Bosch-Domènech; Joaquim Silvestre (University of California, Department of Economics, 2012)
Various experimental procedures aimed at measuring individual risk aversion involve a list of pairs of alternative prospects. We first study the widely used method by Holt and Laury (2002), for which we find that the removal of some items from the lists yields a systematic decrease in risk aversion. This bias is quite distinct from other confounds that have been previously observed in the use of the Holt and Laury method. It may be related to empirical phenomena and theoretical developments where better prospects increase risk aversion. Nevertheless, we have also found that the more recent elicitation method due to Abdellaoui et al. (2011), also based on lists, does not display any statistically significant bias when the corresponding items of the list are removed. Our results suggest that methods other than the popular Holt and Laury one may be preferable for the measurement of risk aversion.
Keywords: C91; 330; risk aversion; risk attitudes; experiments; lists; elicitation method; Holt; Laury; Abdellaoui; Driouchi; l'Haridon; independence axiom